The role of dietary flavonoids for modulation of ATP binding cassette transporter mediated multidrug resistance. Issue 5 (31st December 2021) - Teng, Hui; Deng, Hongting; He, Yuanju; Lv, Qiyan; Chen, Lei
Abstract : Flavonoids are widely existing compounds with enormous pharmacological effects from food and medicine. However, the low bioavailability in intestinal absorption and metabolism limits their clinical application. Intestinal efflux ABC (ATP binding cassette) transporters, including P‐glycoprotein (P‐gp), breast cancer resistance protein (BCRP) and multidrug resistance‐ associated proteins (MRPs), act as ''pumping doors" to regulate the efflux of flavonoids from intestinal epithelial cells into the intestinal cavity or the systemic circulation. The present review describes the critical effect of ABC transporters involved in the efflux of flavonoids which depend on its efflux direction. And the role of flavonoids for modulation of intestinal ABC transporters was emphasized and several examples were given. We summarized that the resistance effect of flavonoid‐mediated multidrug on ABC transporters may influence the bioavailability of drugs, bioactive ingredients and/or toxic compounds upon dietary uptake. Meanwhile, flavonoids functionalized as reversing agents of the ABC transporter maybe an important mechanism for unexpected food‐drug, food‐toxin or food‐food interactions. The overview also indicates that elucidation of the action and mechanism of the intestinal metabolic enzymes‐efflux transporters coupling will lay a foundation for improving the bioavailability of flavonoids in vivo and increasing their clinical efficacy.